Comparative demographics of the European cystic fibrosis population: a cross-sectional database analysis - McCormick, Jonathan D.; Mehta, Gita R.; Olesen, Hanne Vebert Ebert; Viviani, Laura; Macek, Milan St; Mehta, Anil; Yiallouros, Panayiotis K. (My University, 2010)
Background: Country-specific patients' registries are rarely used to make international comparisons because of protocol discrepancies in data collation. We present data from a European cystic fibrosis registry that is dedicated to collection of demographic data, and assess whether the resources available in countries with and without European Union (EU) membership affects care and survival of patients. Methods: Data for demographic indicators-age, age at diagnosis, sex, and genotype-for patients with cystic fibrosis from 35 European countries were combined, and used to establish the differences in demographic indicators between EU and non-EU countries. EU membership status in 2003 was used to divide countries. We modelled demographic indicators of EU countries on non-EU countries to estimate the size of the cystic fibrosis population if non-EU countries had had the same resources available for patients as did EU countries. Findings: Data were gathered for 29 025 patients, who had a median age of 16·3 years (IQR 8·9-24·8), with a difference of 4·9 years (95% CI 4·4-5·1; p<0·0001) between EU (median 17·0 years, IQR 9·5-25·6) and non-EU countries (12·1 years, 6·0-19·2). The proportion of patients older than 40 years was higher in EU countries (1205 [5%]) than in non-EU countries (76 [2%]), with an odds ratio of 2·4 (95% CI 1·9-3·0, p<0·0001). We estimated that the cystic fibrosis population in non-EU countries would increase by 84% if patients had a demographic profile comparable to that of patients in EU countries. Interpretation: Future studies need to establish the reasons for the lower proportion of patients with cystic fibrosis in non-EU countries than in EU countries, such as underdiagnosis and premature childhood mortality. Funding: European Community's Sixth Framework Programme for Research, and Czech Ministry of Health.
Keywords: Lung; Pulmonary exacerbation; Cystic fibrosis